1997
DOI: 10.1006/jipa.1997.4692
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility of Cultured Shrimp (Penaeus vannamei) to Infectious Hypodermal and Hematopoietic Necrosis Virus andBaculovirus penaei:Possible Relationship with Growth Status and Metabolic Gene Expression

Abstract: Offspring of four crosses (I, II, III, and IV) of Penaeus vannamei from known high-and low-growth families were challenged with infectious hypodermal and hematopoietic necrosis virus (IHHNV) and Baculovirus penaei (BP) to compare their susceptibility to these viral agents and examine the genetic component involved in disease resistance or susceptibility. Family crosses were made using broodstock from five families developed by the U.S. Marine Shrimp Farming Program. The prevalence of IHHNV infection was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…The latter species soon became the main cultured species since the late 1980s ( Lotz 1997 ). This virus has affected other penaeid species in the Pacific ( Alcivar-Warren et al 1997 ) and various countries in America, Asia and Oceania ( Lightner 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…The latter species soon became the main cultured species since the late 1980s ( Lotz 1997 ). This virus has affected other penaeid species in the Pacific ( Alcivar-Warren et al 1997 ) and various countries in America, Asia and Oceania ( Lightner 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that selective breeding results in reduced antibody diversity in fish (Sommer 2005;Spielman et al 2007), and could therefore reduce vaccine competence. Host immunity to one pathogen can also have tradeoffs with susceptibility to another (Ehlinger 1977;Alcivar-Warren et al 1997). There was some indication of this here because the ARS-Fp-R line, which has been bred for resistance to bacterial coldwater disease, suffered more mortality than the IHNV.R line.…”
Section: Discussionmentioning
confidence: 99%
“…Genetics Offspring of male and female crosses of high-growth and low-growth "families" of a well-defined population at GCRL Consortium at OI, Hawaii, were fed BP as 15-day-old postlarvae (PL15s) (Alcivar-Warren et al 1997). The high  high-growth and low  high-growth (female  male) postlarvae, respectively, had a 77 and 85 % survival rate at 18 days postexposure compared with 19 and 24 % survival for the low  low-growth and high  low-growth offspring.…”
Section: Host Factorsmentioning
confidence: 99%